Fully developed MHD mixed convective flow through a composite system in a vertical channel. (3rd October 2021) - Ojha, Kanaka Lata; Barik, Nikunja Bihari; Dash, G. C.; Das, M.
Abstract: A mixed convective momentum and heat transfer in a composite system, consisting of electrically conducting fluid and saturated porous medium in a vertical channel, have been studied. The flow, subjected to a linearly varying space dependent wall temperature engenders a convection current in the flow domain. The present study accounts for the effects of viscosities, and electrical conductivities of both the regions. The Brinkman model has been used to model the flow through porous region. The novel results of the analysis are: the simulation of external magnetic field (control input) in porous region affects momentum transport in both the regions; the amount of resistivity developed in primary velocity due to application of magnetic field can be experienced in the clear-fluid region by applying nearly 50 percent less magnetic field strength in conjunction with requisite porosity of the saturated porous medium; porous matrix is having higher thermal diffusivity than clear fluid provided bounding surfaces are of the same material.